Gravimetric Estimation of Ni(II) and Cu(II) Ions with Bis-Salicylidene-Ethylene Diamine - Kumari, Sangita; Prasad Yadav, Siteshwar; Kumar Das, Anil; Mishra, P.M. (Asian Journal of Chemistry, 2010)
Gravimetric estimation of Ni(II) and Cu(II) ions with bis-salicylidene- ethylene diamine was performed in ammonical medium. The complexes are square-planar in geometry. The complexes have been characterized on the basis of elemental analysis, magnetic susceptibility, molar conductance and spectral data.